6(2v-2)=96

Simple and best practice solution for 6(2v-2)=96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2v-2)=96 equation:


Simplifying
6(2v + -2) = 96

Reorder the terms:
6(-2 + 2v) = 96
(-2 * 6 + 2v * 6) = 96
(-12 + 12v) = 96

Solving
-12 + 12v = 96

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 12v = 96 + 12

Combine like terms: -12 + 12 = 0
0 + 12v = 96 + 12
12v = 96 + 12

Combine like terms: 96 + 12 = 108
12v = 108

Divide each side by '12'.
v = 9

Simplifying
v = 9

See similar equations:

| 40b+10=210 | | (2x+10)+5x+140= | | 3(8-4x)=84 | | 4x-13-35=0 | | 3x+90=450 | | 2(x+5)(x-1)= | | 7+9+n=-9+2n+n | | 4*x^2+4*y^2-y^3=0 | | 4c-36=-8 | | y+26-8=40 | | 93=16-5p | | -12x-4=56 | | 6k-15=-33 | | 5x^2+y^2=21 | | 6x-3=17+4x | | 12/21 | | (x-3)2=12 | | 88/8 | | log(2)(5x-5)=4 | | 3x+-2=5+-3 | | 3y+1=4y+11 | | -3/5(20r-5)-(-6r) | | (x+2)(3x-1)=6 | | 14+14+11+11+12+9+15+16+13= | | 2w^2-13+15= | | (x^2y/x^5)^3 | | Y=1/3x-100 | | 1/3×251.2 | | 8y-30-2y=6(y-5) | | 8y+14-1y=7(y+2) | | 60=20/x | | 8y+14=7(y+2) |

Equations solver categories